A Detailed Spatial Expression Analysis of Wing Phenotypes Reveals Novel Patterns of Odorant Binding Proteins in the Soybean Aphid, Aphis glycines - Wang, Ling; Yin, Hang; Zhu, Zhiguo; Yang, Shuai; Fan, Jia (Frontiers in Physiology, 2021)
The wide range of insect niches has led to rapid expansion, relatively independent evolution, and high variation in chemosensory gene families. Previous studies have revealed some OBP functions in processes beyond olfaction, such as gustation and reproduction. In the present study, a detailed comparative transcriptomic analysis strategy was applied in the soybean aphid, Aphis glycines, which focused on various functional tissues or organs of winged aphids, including the antenna, head, leg, wing, thorax, cauda and cornicle. Detailed spatial OBP expression patterns in both winged and wingless parthenogenetic aphids were further detected by qPCR. Twelve OBPs, including three new OBPs, were identified. They all showed comparatively higher expression in sensory organs or tissues, such as the antenna, head, or leg. Additionally, we report some novel expression patterns of aphid OBPs for the first time. 1. Five and five OBPs exhibited high expression levels in the cauda and cornicle, respectively. As the cornicle is the alarm pheromone (E-β-farnesene, EBF) storage and release organ, it was not surprising to find all previously reported EBF binding proteins (OBP3, OBP7, and OBP9) in this organ. 2. Three OBPs were highly expressed in the wing. 3. Two OBPs were significantly more highly expressed in the wingless thorax than in the winged thorax with the wings removed, and their transcripts were significantly enriched in the removed wings. Additional details of OBP spatial expression were revealed under our strategy, which implied the existence of carrier transport functions other than carrying foreign chemicals and therefore broader ligand ranges of insect OBPs. It would be helpful to understand how insect OBPs function in chemical perception as well as other potential physiological functions of OBPs. Key words: Odorant binding protein, wing phynotype, Aphis glycines, expression pattern analysis, cauda, cornicle, antenna, wing, leg, head, thorax